Psychological Well-Being in First-Cycle Students at a Private University in Lima - Rodríguez Flores, Eduar Antonio (2022)
The distance education modality, added to the demands of the university environment, can generate states of anxiety and uncertainty in students. Given this, an investigation was carried out whose objective was to describe the psychological well-being of first cycle university students. This is a descriptive case study, with a qualitative approach and phenomenological design. The research was carried out between March and August 2021 and was aimed at 20 students and 10 teachers from the Faculty of Health Sciences of a private university in Lima. For data collection, a focus group guide for teachers and a semi-structured interview guide for students were applied. Among the findings, the recognition of six central interrelated categories stands out: self-acceptance, purpose in life, autonomy, mastery of the environment, positive relationships, and personal growth. In general terms, the students' favorable state of psychological well-being was evidenced, related to a positive classroom climate, as well as a favorable self-perception. However, certain weaknesses were identified, such as the inability to take responsibility for their own actions, and the lack of short, medium, and long-term goals. In conclusion, the results have made it possible to describe the psychological well-being of the students who were part of the study sample, which has made it possible to identify the strengths and opportunities for improvement that should be considered for future studies, as well as the design of targeted proposals to improve the problem situation.